Solve thermal explosion model by central difference and Newton iteration method - Xijian Wang; Tonghua Zeng (Statistics, Optimization & Information Computing, 2015)
In this paper, the general equation form of a thermal explosion in a vessel with boundary values is firstly presented, later the central difference method and Newton iteration method are used to solve the relevant partial differential equations in one-dimensional and two-dimensional forms, finally the order of convergence of the numerical scheme is verified by numerical experiments and the experiment results are provided.